Clinical profiles and molecular genetic analyses of 98 Chinese children with short statures - Fang, Danfeng; Li, Xing; Zhang, Zhigang; Cai, Hefei; Wang, Lu; Yu, Jiahe; Hu, Xuanye; Ye, Bin (Frontiers in Genetics, 2024)
Background: Short stature is one of the most prevalent endocrine disorders in children. The genetic basis of short stature is a complex and actively researched concern. Currently, genetic research on exome sequencing for short stature is limited, and more large-scale studies are necessary for further exploration. Methods: This retrospective study investigated 98 Chinese children with short stature (height SDS ≤ -2.5) of unknown etiology, recruited between 2017 and 2021. Whole exome sequencing (WES) was performed on these patients to identify potential genetic etiologies. Clinical data were retrospectively reviewed to assess the pathogenicity of the identified mutations. Additionally, 31 patients consented to and received recombinant human growth hormone (rhGH) therapy for 12 months.The short-term effects of rhGH treatment were evaluated across different etiologies of short stature patients. Results: WES identified 31 different variants in 18 genes among 24 (24.5%) patients . Individuals with a more severe short stature tend to have a higher likelihood of finding a genetic etiology. Short stature, accompanied by other phenotypes , had a significantly higher diagnostic yield compared to simple severe short stature. The rhGH therapy demonstrated efficacy in most children. Nevertheless, treatment response was suboptimal in a boy diagnosed with 3M syndrome. Conclusion: WES emerged as an important approach to confirm genetic disorders in patients with severe short stature of unknown etiology and suggests that WES could be used as a primary diagnostic strategy. The rhGH administration may not be suitable